Index, Volume 78 - 2007 : subject / Indeks, Jaargang 78 - 2007 : onderwerp - Index Subject (Journal of the South African Veterinary Association, 2007)
Comparison of quality of induction of anaesthesia between intramuscularly administered ketamine, intravenously administered ketamine and intravenously administered propofol in xylazine premedicated cats